Potential drug-drug interactions among elderly in-patients with cardiac illness at a tertiary care centre - Mathur, Akanksha; Jain, Nidhi; Sharma, Achal; Shah, Prashant C. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Drug interactions are major cause of concern in hospitalized patients with cardiac illness especially in elderly population. Therefore, the study was conducted to determine the prevalence and pattern of potential drug-drug interactions (pDDI) and risk factors, if any. Methods: It was a prospective observational study involving 75 elderly in-patients with cardiac diseases. IHEC approval was taken before commencement of study and written informed consent was taken from all the study participants. Data was collected using structured data collection tool. pDDI were analyzed using MEDSCAPE databse. Data was analyzed using SPSS 20.0 in terms of descriptive statistics. Pearson correlation coefficient was used to find the association between the risk factors and potential DDIs. P value of ≤0.05 was considered statistically significant. Results: The prevalence of pDDI was found to be 100%. Total 593 pDDI and 33 interacting drug pairs were observed in the study. The common drug interacting pairs were aspirin and furosemide 140 (23.61%), followed by aspirin+ enalapril 98 (16.53%) and heparin and clopidogrel 56 (9.44%). Majority of pDDI 480 (81%) were found to be of moderate severity. A significant association was documented between length of hospital stay (p=0.041) and occurrence of pDDI. A statistically significant correlation (r =0.621; p<0.01) was noted between number of drugs prescribed and total number of pDDIs. Conclusions: A high prevalence of pDDI was observed. The prevalence rate is directly related to number of drugs prescribed and length of hospital stay. Therefore, close monitoring of hospitalized patients is recommended.